Treachery Reflected In Henrik Ibsen's Public Enemy (1882)Drama: An Individual Psychological Approach - Herdianto, Pradika Guslan; , Dr. Phil. Dewi Candraningrum, M.Ed; , Titis Setyabudi, S.S. M. Hum (2015)
SUMMARY PRADIKA GUSLAN HERDIANTO. A320110197. TREACHERY REFLECTED IN HENRIK IBSEN'S PUBLIC ENEMY (1882) DRAMA: AN INDIVIDUAL PSYCHOLOGICAL APPROACH. Research Paper. School of Teacher Training and Education, Muhammadiyah University of Surakarta. August 2, 2015. The major problem of this study is treachery. Someone who suddenly has treachery nature, he must experience a big change in his life. The objective of this study is to analyze Henrik Ibsen‟s Public Enemy based on the structural elements and analyze this drama based on the Individual Psychological Approach. The Writer employs qualitative method. The writer uses two data sources: primary and secondary. The primary data source of the study is Public Enemy drama by Henrik Ibsen. Secondary data are the supporting data taken from literary books, criticism, and some articles related to the drama. The secondary data of the study are taken from any information related to the drama. The method of data collection is the researcher will employ the descriptive qualitative research. Based on the analysis, the researcher gets some conclusions. The study shows that the problem faced by the minor character is his treachery. It is proven by his dream that becomes success. He is an editor. He wants to be a success man in the life. Someday, Dr. Stockmann gets big news for the town, Hovstad wants get many advantages from that news, so he becomes Dr. Stockmann‟s side. But, the Mayor didn‟t agree with that news, so Hovstad betrays Dr. Stockmann and becomes the Mayor‟s side. Finally, Hovstad opposes Dr. Stockmann.